Microstructural and textural characteristics of soy protein isolate and tara gum cold-set gels - Ingrassia, Romina (2019)
Soy protein isolates (SPI) are capable of forming cold-set gels. This techno-functional property can be affected by the presence of tara gum (TG). Under certain conditions, these SPI/TG systems may also form water-in-water (W/W) emulsions. The aim of this study was to evaluate acid gels formed from soy protein isolates (SPI) and tara gum (TG) aqueous mixtures, and to find the conditions in which the W/W emulsions of SPI droplets dispersed in a TG continuous phase can be stabilized by SPI gelation as a strategy to prevent emulsion destabilization. Cold-set gels of SPI 0.3 g/L at different TG concentrations (0–0.05 g/L) showed different microstructures, a consequence of a different balance between gelation and segregative phase separation processes. SPI gels showed a homogenous and compact microstructure. When TG was present at 0.01 g/L and 0.02 g/L, the protein network was less interconnected, showing coarse-stranded and bicontinuous gels, respectively. At TG > 0.03 g/L, stable W/W emulsions were formed, revealing an abrupt decrease in gel firmness, a significant loss of fracture capacity, and a decrease in the water holding capacity. These findings may be used as a starting point for the application of these gelled systems as thickeners, texture modifiers, and coating materials for delivery of bioactive compounds.